Dismissed Possibilities: Thingness, Posthumanism and Corporeal Feminism in Angela Carter’s Nights at the Circus - Özge Öz (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
In Angela Carter’s Nights at the Circus (1984), the protagonist Fevvers is a character with an overwhelming bodily presence, whose identity is mediated through her bodily performances and via the viewership of the spectacle that is her “self”. Always facing the question “Is she fact or is she a fiction?”, the real identity and being of Fevvers seems to escape the reader through her magnified corporeality and performativity. Yet, as the episodes in which Fevvers performs as inanimate objects or is juxtaposed next to them show, the corporeal existence of Fevvers harbors many posthuman possibilities for subjectivity, even though Fevvers is also discovered to be severely marked by her human identity and femininity. Using a theoretical framework informed by writings on thing theory, posthumanism, and posthuman feminism, this paper explores the hybrid bodily existence of Fevvers from a post humanist angle to point out that despite demonstrating a general intuition towards a posthuman understanding of subjectivity and feminism as also claimed by former critics, Nights at the Circus finally dismisses such possibilities for a “corporeal feminism” as manifestoed by Elizabeth Grozs. Staying loyal to her human nature, the novel’s protagonist Fevvers turns down possibilities offered by her animal, thing, and machine beings and subsumes her hybridity under corporeal feminism.